PENGEMBANGAN SEKOLAH BERTARAF INTERNASIONAL MELALUI ORGANISASI BELAJAR: KONSEP DAN IMPLEMENTASI - Suyanto, Slamet (Jurnal Cakrawala Pendidikan, 2010)
Abstract Indonesian Government, putting into action the Educational System Law, is starting its efforts this year to develop schools to reach international standard schools (SBI). The Educational System Law (2003), specifically act number 20, states that “The government and/or district develop at least one school in every level to be promoted into an international standard school (SBI)”. That act arises many questions in the school level concerning the international standards school (SBI), such as what is SBI, what is the main goal, what is the requirement of schools to be promoted as SBI, how can schools develop themselves to reach SBI, what is the criterion of the success? Indeed, there are many ways for schools to develop themselves into an international level. Every school may use a different way that suitable to the school’s condition. This paper brings to mind the Learning Organization (LO) as one of the generic promising ways to develop a school into an international level. LO is basically an organization that learns and does continuously improvement. LO comprises of five major components: (1) shared vision, (2) system thinking, (3) personal mastery, (4) mental models, and (5) team learning. Besides, there are five subsystems where those components should be developed in LO: (1) learning, (2) knowledge, (3) technology, (4) people, dan (5) organization. Keywords: SBI, organisasi belajar, learning organization